Comparative study on the bioavailability and bioequivalence of rifapentine capsules in humans - Qi, Ying; Zhao, Pengfei (Frontiers in Pharmacology, 2025)
Introduction: Rifapentine, a potent semi-synthetic member of the rifamycin class, is approved for the treatment of tuberculosis due to its effective bactericidal properties. It is essential to assess the bioequivalence and bioavailability of different rifapentine formulations to ensure consistent clinical outcomes. This study compares the pharmacokinetic profiles of test and reference rifapentine capsules in healthy male volunteers.MethodsIn this single-dose, randomized, crossover study, 19 healthy male volunteers aged 18–40 received 0.6 g of either the test or reference rifapentine capsules. The reference is an NMPA-approved product, while the test is a modified version intended to match it in safety and efficacy; both contain the same active ingredient but may differ in excipients or manufacturing processes. Blood samples were collected at predefined intervals over a 84-h period following administration to measure rifapentine plasma concentrations using UPLC. Key pharmacokinetic parameters, including maximum concentration (Cmax), time to maximum concentration (Tmax), and area under the concentration-time curve (AUC), were calculated and analyzed for bioequivalence.ResultsThe pharmacokinetic analysis demonstrated that both formulations of rifapentine had similar absorption rates and extent of exposure. The mean Cmax, Tmax, and AUC values were closely aligned between the two formulations. Statistical analysis, including ANOVA and bioequivalence testing, confirmed that the 90% confidence intervals for the primary pharmacokinetic parameters (Cmax, AUC0-t, and AUC0-∞) fell within the acceptable range of 80%–125% for bioequivalence. Both formulations were well-tolerated with no serious adverse events reported.DiscussionThe results of this study confirm the bioequivalence of the test and reference formulations of rifapentine under the conditions tested. These findings support the interchangeable use of these formulations in clinical practice for the treatment of tuberculosis. This study contributes to the body of evidence needed to ensure that patients receive a consistent therapeutic effect when administered either formulation of rifapentine.ConclusionThe bioequivalence demonstrated between the test and reference rifapentine capsules supports their use in clinical settings where rifapentine is indicated for tuberculosis therapy. This study provides a robust foundation for the regulatory approval of generic formulations of rifapentine, ensuring that patients have access to effective and lower-cost medication options.